Civil societies' reactions of East- and Southeast Asian countries to the Russian war on Ukraine: Preliminary observations - David M. Malitz; Surachanee Sriyai (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2022)
Undoubtedly, the war in Ukraine has far-reaching political and economic implications for many regions of the world, including East and Southeast Asia. The governments' reactions to the war have varied considerably ranging from fully supporting Ukraine in alliance with the United States and the European Union, as Japan and Korea have done, to the full backing of Russia by North Korea and Myanmar. That said, many governments in Southeast Asia remain neutral. Nonetheless, the responses to the war in the public spheres neither necessarily agree with their respective governments' stances, nor are they expected to be homogenous. This collection of articles serves as a preliminary attempt to take stock of the reactions of selected civil societies in East and Southeast Asian countries to Russia's invasion of Ukraine in February 2022 by analyzing the respective countries' public sentiment through press and social media. While the reactions of the publics of East and Southeast Asian societies have no direct influence on global society, they will shape their governments' future courses, where they can be expressed and where elections are held. As the long-term consequences of the geopolitical and economic shifts initiated by this conflict will only slowly become fully discernible, their analysis is of great interest. The papers have been presented and discussed at an online workshop jointly organized by the Institute of East Asian Studies at the University of Duisburg-Essen (IN-EAST), the German Institute of Japanese Studies, Tokyo (DIJ), the Chair of Transregional Southeast Asian Studies at Humboldt University Berlin, and the Faculty of Political Science, Chulalongkorn University, Bangkok.
Keywords: 330; Ukraine; East Asia; ASEAN; Southeast Asia; civil society; public opinions